Molecular insight into the genomic variation of SARS-CoV-2 strains from current outbreak. (August 2021) - Das, Avizit; Khurshid, Sarah; Ferdausi, Aleya; Nipu, Eshita Sadhak; Das, Amit; Ahmed, Fee Faysal
Graphical abstract: Highlights: Genomic variation analysis of 715 SARS-CoV-2 genome sequences from 39 countries was performed. A total of 164 variants were identified based on 108 SNPs. Ancestral type of SARS-CoV-2 were most prevalent in China while A104 and A52 in USA and Japan respectively. Most non-synonymous SNPs were located in nucleocapsid phosphoprotein, Nsp3 and spike glycoprotein encoding gene. Molecular divergence revealed the phylogenetic relation of SARS-CoV-2 to Yunnan 2013 bat strain. Abstract: Coronavirus disease 2019 (COVID-19) is the newly emerging viral disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The epidemic sparked in December 2019 at Wuhan city, China that causes a large global outbreak and a major public health catastrophe. Till now, more than 129 million positive cases have been reported in which more than 2.81 million were dead, surveyed by Johns Hopkins University, USA. The diverse symptoms of COVID-19 and an increased number of positive cases throughout the world hypothesize that this virus assembles more variants that are preventing the pursuit of its adequate treatment as well as the development of the vaccine. In this study, 715 SARS-CoV-2 genomes were retrieved from the gisaid and NCBI viral resources involving 39 countries and 164 different types of variants were identified based on 108 Single Nucleotide Polymorphisms (SNPs) in which the ancestral type of SARS-CoV-2 was found as the most frequent and the most prevalent in China. Moreover, variant type A104 was identified as the most frequent in the USA and A52 in Japan. The study also recognized the most common SNPs such as 241, 3037, 8782, 11083, 14408, 23403, and 28144 as well as variants regarding base-pair, C > T. A total of 65 non-synonymous SNPs were recognized which were mostly located in nucleocapsid phosphoprotein, Non-structural protein 3(Nsp3), and spike glycoprotein encoding gene. Molecular divergence analysis revealed that this virus was phylogenetically related to Yunnan 2013 bat strain. This study indicates SARS-CoV-2 frequently alters their genetic material, which mostly affects the nucleocapsid phosphoprotein, and spike glycoprotein-encoding gene and makes it very challenging to develop SARS-Cov-2 vaccine and antibody-mediated rapid diagnostic kit.